The Effect of Competence and Corporate Culture on Employee Performance at the Suwendho Rinaldy and Rekan Public Appraisal Services Office, Jakarta Branch through Motivation as a Mediating Variable. - Setya Agung Prakoso; Pasaribu, Bomer; Muhammad Irawan Noor (Madani Connection, 2024)
This study investigates several key relationships within the workplace environment at the Suwendho Rinaldy and Rekan Public Appraisal Services Office in Jakarta. The objectives are to 1) analyze the influence of competence and corporate culture on motivation. 2) analyze the influence of competence and corporate culture on employee performance. 3) analyze the influence of motivation on employee performance. 4) analyze the influence of competence on employee performance through motivation 5) analyze the influence of corporate culture on employee performance through motivation. The results: 1) there is a positive and significant influence both partially and simultaneously between competence and corporate culture on employee work motivation, 2) there is a positive and significant influence both partially and simultaneously between competence and corporate culture on employee performance, 3) there is a positive and significant influence between motivation on employee performance, 4) competency factors influence employee performance through motivation 5) corporate culture factors do not influence employee performance through motivation.